Parent and peer pathways linking childhood experiences of abuse with marijuana use in adolescence and adulthood. (March 2017) - Alex Mason, W.; Jean Russo, M.; Chmelka, Mary B.; Herrenkohl, Roy C.; Herrenkohl, Todd I.
Abstract: Introduction: The social developmental processes by which child maltreatment increases risk for marijuana use are understudied. This study examined hypothesized parent and peer pathways linking preschool abuse and sexual abuse with adolescent and adult marijuana use. Methods: Analyses used data from the Lehigh Longitudinal Study. Measures included child abuse (physical abuse, emotional abuse, domestic violence, and neglect) in preschool, sexual abuse up to age 18, adolescent (average age = 18 years) parental attachment and peer marijuana approval/use, as well as adolescent and adult (average age = 36 years) marijuana use. Results: Confirming elevated risk due to child maltreatment, path analysis showed that sexual abuse was positively related to adolescent marijuana use, whereas preschool abuse was positively related to adult marijuana use. In support of mediation, it was found that both forms of maltreatment were negatively related to parental attachment, which was negatively related, in turn, to having peers who use and approve of marijuana use. Peer marijuana approval/use was a strong positive predictor of adolescent marijuana use, which was a strong positive predictor, in turn, of adult marijuana use. Conclusions: Results support social developmental theories that hypothesize a sequence of events leading from child maltreatment experiences to lower levels of parental attachment and, in turn, higher levels of involvement with pro-marijuana peers and, ultimately, to both adolescent and adult marijuana use. This sequence of events suggests developmentally-timed intervention activities designed to prevent maltreatment as well as the initiation and progression of marijuana use among vulnerable individuals. Highlights: The mechanisms linking child maltreatment with later marijuana use are uncertain This longitudinal study tested parent and peer social developmental mechanisms Preschool abuse and sexual abuse were negatively related to parental attachment Parental attachment was negatively related, in turn, to peer marijuana use Peer marijuana use predicted adolescent and, in turn, adult marijuana use